2014
DOI: 10.1155/2014/641849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Metal Contaminants on the Stability of Castor Oil Methyl Ester

Abstract: This study investigates the effect of iron (Fe) and aluminium (Al) contaminants on the stability of castor oil methyl ester (COME). COME was synthesized via transesterification reaction and the peroxide value of the COME was used to monitor its stability. Varied amounts of Fe and Al (0.2 g, 0.4 g, 0.6 g, 0.8 g, and 1.0 g) in powdered form were added to 100 mL of COME and their effect on the peroxide value was monitored for a day, for the first phase of the experiment, while for the second phase, 0.3 g and 0.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…NO x formation takes place in very high temperature. It is observed that the NO x emission was more in biodiesel as compared to diesel as it has high flash and fire point; however the use of additives reduced the NO x emissions as they inhibit the formation of free radicals [21]. Figure 8 illustrates the variation of NO x emissions and the load with neat diesel and various blends of biodiesel with and without contaminants.…”
Section: No X Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO x formation takes place in very high temperature. It is observed that the NO x emission was more in biodiesel as compared to diesel as it has high flash and fire point; however the use of additives reduced the NO x emissions as they inhibit the formation of free radicals [21]. Figure 8 illustrates the variation of NO x emissions and the load with neat diesel and various blends of biodiesel with and without contaminants.…”
Section: No X Emissionmentioning
confidence: 99%
“…In addition, copper was found to be showing most catalytic behaviour for oxidation of biodiesel. Akhabue et al [21] compares Fe and Al over the stability of castor oil methyl ester, Experimental study shows Fe provided better stability as compared to Al. With the rate of increase of metal contaminants, the rate of decomposition hydro peroxides was more than the rate of formation of hydro peroxides.…”
Section: Introductionmentioning
confidence: 99%